Three Essays on the single currency of ECOWAS and the associated challenges - (:unkn) unknown (My University, 2012)
The context of the globalization suggests that the project of a West African common currency launched by the ECOWAS commission in 1999 is a potential source of opportunities for the small economies of the sub-Region. The common market will increase the scale of their small domestic markets; facilitate the realization of the scale economies; enhance the profitability of the investments and improve the potential product of the economies. Thus, this thesis aims to analyse the effect of that monetary evolution planned for countries following an autonomous monetary and exchange policy in the West African sub-Region. The results show that the economies of the sub-Region are not symmetric, especially because of their growth cycles. The equilibrium exchange rate analyse proves that the non-Participation in the common currency does not shield the West African economies against the exchange rate misalignment for them. Especially a participation of Gambia, Guinea or Sierra-Leone in the West African Economic and Monetary Union (WAEMU) between 1994 and 1999 would have generated a lower exchange rate misalignment for them. But that effect decreases or disappears as for 2000. On another hand, the participation in a common currency or in a monetary area in Sub-Saharian Africa does not affect the welfare measured by growth or HDI. But, both the participation in the monetary area or in the common currency improves the welfare, measured by consumption by head, strongly and significantly. Ultimately the ECOWAS economies are not robustly symmetric. Relative to the misalignment of the exchange rate the non-Participation in the WAEMU is not better, except for Ghana and Nigeria. For all ECOWAS economies, the participation in a common currency or in a monetary area is better for their welfare, measured by the consumption by head. The ECOWAS common currency project is subsequently relevant for monetary union non-Participants economies of the sub-Region.
Keywords: African Research